Strengthening organizational capacity to enhance the sustainability of ornamental fish community cooperatives-based in Malang - Fadillah Putra; Mikchaell Alfanov Pardamean Panjaitan; Fajar Shodiq Ramadhan Ramdlan (Universitas Muhammadiyah Malang, 2023)
Cooperatives play a crucial role in the Indonesian economy, cooperatives have high values in helping to improve the country's economic welfare. Therefore, the development of a cooperative-based Indonesian economy is urgently needed to help boost the economy. Partners in this service activity are the Nusantara Ornamental Fish Malang community. Institutional strengthening is very influential in developing cooperative-based community businesses. This is based on the problems found in the form of weak ornamental fish community institutional systems, more optimal ornamental fish production, limited access to capital, and limited access to ornamental fish marketing. This service activity aims to provide knowledge and assistance in strengthening cooperative-based community business institutions. Assistance provided in the form of cooperative training and procedures for its establishment, cooperative management, facilities for procuring ornamental fish seeds, and ornamental fish marketing galleries. The result is the formation of an ornamental fish production cooperative that can run well and it is hoped that it will be able to help cooperative members and fish farmers in dealing with various problems including access to capital and assistance from the government.